Cellulase production by Trichoderma reesei Rut C-30 from different cellulosic substrates. - Colina, Alejandro; Ferrer, Alexis; Urribarrí, Lauris (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> Cellulase production by the fungus Trichoderma reesei Rut C-30 (ATCC 56765) at initial pH 4.8, with different cellulosic substrates (rice straw, cellulose as the only carbon source, and a mixture of commercial cellulose and hemicellulose), was investigated. Previously, growth and sporulation of the fungus on potato agar plates with different glucose concentrations, and different variations of the Mandels and WeberÂ´s mineral solution (1969) for the germination and development of conidiospores of T. reesei, were studied. Fermentations were carried out in duplicate, in 250 mL Erlenmeyer flasks with 60 mL of mineral solution, 1% w/v substrate, 29°C and agitation at 200 rpm for 120 h, and in a 5L Bioflo III fermentor with rice straw as the substrate, under controlled temperature (29°C), agitation (150 rpm) and aeration (20% saturation) conditions. The chemical nature of the rice straw (6.75% protein) and the commercial substrates (0% protein, control substrate) used in the fermentations played a major role in the final pH. However, the difference between the pH values reached at the end of the fermentations (between 3.28 and 6.38), did not greatly affect the growth and cellulase production by the fungus in spite of the fact that the growth was much greater with the commercial substrates. The cellulase production was higher in the fermentations with the commercial mixture (0.62 IU/mL), followed by those with amorphous cellulose as the only carbon source (0.57 IU/mL) and rice straw (0.51 IU/mL). Cellulase production in the fermentor (0.38 IU/mL) was lower than that found in the flasks study.